2011
DOI: 10.1093/europace/eur345
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of DDD and VDD pacing: a prospective non-randomized single-centre comparison of patients with symptomatic atrioventricular block

Abstract: Comparing VDD and DDD pacing, a significantly larger number of VDD-paced patients developed poor atrial signal detection without clinical impact. However, atrial under sensing did not influence the incidence of atrial fibrillation, myocardial infarction, dilated cardiomyopathy, or mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
27
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 32 publications
3
27
1
2
Order By: Relevance
“…Our findings were consistent with that reported by Marchandise et al, [19] showing that although a significantly larger number of VDD-paced patients developed poor atrial signal detection compared to DDD, the risk of mortality was similar. Compared to the study performed by Marchandise et al, the present study enrolled more patients to investigate this issue and may be able to lower the possibility of a type 2 error (false negative results due to limited sample size).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings were consistent with that reported by Marchandise et al, [19] showing that although a significantly larger number of VDD-paced patients developed poor atrial signal detection compared to DDD, the risk of mortality was similar. Compared to the study performed by Marchandise et al, the present study enrolled more patients to investigate this issue and may be able to lower the possibility of a type 2 error (false negative results due to limited sample size).…”
Section: Discussionsupporting
confidence: 93%
“…[8] Santini et al [4] reported stable atrial signals over time in every physical activity, while extensive variation of atrial signal amplitude between postures was reported in another study. [18] Marchandise et al [19] found that up to one-third of VDD pacemaker patients could not maintain good atrial sensing after a mean follow-up of 2 years, which could mostly be ameliorated by increasing the atrial sensitivity. In the previous report from our group, inappropriate atrial sensing was noted in 16.6% of patients receiving VDD PPMs after a follow-up of 4.9 ± 2.5 years.…”
Section: Discussionmentioning
confidence: 99%
“…First, in the cited Marchandise et al paper, atrial sensing in VDD is poorer than in DDD, but the VDD systems are older and there is no clinical impact.…”
mentioning
confidence: 99%
“…Low and variable atrial amplitudes in a VDD lead have a problem of oversensing of far‐field R wave or undersensing of low‐amplitude atrial EGM, which can cause inaccurate discrimination of VT as SVT and vice versa. Marchandise et al in their study of 420 patients of atrioventricular block subjected for VDD or DDD pacing found that good atrial sensing is not maintained in 19% of VDD pacemakers at a mean follow‐up of about 2 years. Most of these failed VDD patients had P‐wave amplitude of <0.5 mV .…”
mentioning
confidence: 99%
“…Marchandise et al in their study of 420 patients of atrioventricular block subjected for VDD or DDD pacing found that good atrial sensing is not maintained in 19% of VDD pacemakers at a mean follow‐up of about 2 years. Most of these failed VDD patients had P‐wave amplitude of <0.5 mV . An inappropriate atrial sensing of 7.3% at 6‐month follow‐up in this study is markedly lower than what is being reported by Marchandise et al, possibly because of amplified atrial amplitude, a characteristic of Lumax 540 VR‐T DX ICD (Biotronik GmbH, Berlin, Germany) .…”
mentioning
confidence: 99%